A companion to paleoanthropology - Begun, David R. (Chichester, West Sussex : John Wiley & Sons Inc., 2013)
"A Companion to Paleoanthropology presents a compendium of readings representing the state-of-the-art in our knowledge relating to the study of ancient humans as found in fossil hominid evidence"--
pt. I. Background to paleoanthropology -- pt. II. The fossil record.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Paleoanthropology; Fossil hominids; Human evolution; Electronic books